2014
DOI: 10.13057/biodiv/d150208
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of trees in tropical dry deciduous forests of Tiruvannamalai district, Tamil Nadu, India

Abstract: Sanjay-Gandhi D, Sundarapandian S. 2014. Inventory of trees in tropical dry deciduous forests of Tiruvannamalai district, Tamil Nadu,. Diversity and distribution patterns of tree species were inventoried in 20 one hectare plots in Sathanur Reserve Forest of Tiruvannamalai district, Tamil Nadu, India. These plots were grouped into three sites based on their location in the reserve forest and the level of disturbance. Site I (8 plots) near to the road and agricultural lands, Site II (8 plots) away from the road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
9
2
Order By: Relevance
“…The species diversity reported in the present study is comparable with the study of Varghese and Balasubramanyan (1999) from a wet evergreen forest of Agastyamalai region in Kerala, Myo et al (2016) from a mixed deciduous and deciduous dipterocarp forests in Madan watershed, Myanmar and Surpam et al (2016) from woodland of Seminary Hills in Nagpur. However, the values obtained here were lower than the studies reported by Giriraj et al (2008) from wet evergreen forests of Kalakkad-Mundanthurai Tiger Reserve, Sahoo and Davidar (2013) from dry deciduous forests dominated by sal in Similipal Tiger Reserve in Odisha, Gandhi and Sundarapandian (2014) from dry deciduous forests of Tiruvannamalai in Tamil Nadu, Mutiso et al (2015) from (Reddy et al 2008;Mohandass et al 2016). In this study, site I is located in an elevation (530-630 m asl) that is higher than that of site II (317-360 m asl), which could be one of the causes for variation in species diversity.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The species diversity reported in the present study is comparable with the study of Varghese and Balasubramanyan (1999) from a wet evergreen forest of Agastyamalai region in Kerala, Myo et al (2016) from a mixed deciduous and deciduous dipterocarp forests in Madan watershed, Myanmar and Surpam et al (2016) from woodland of Seminary Hills in Nagpur. However, the values obtained here were lower than the studies reported by Giriraj et al (2008) from wet evergreen forests of Kalakkad-Mundanthurai Tiger Reserve, Sahoo and Davidar (2013) from dry deciduous forests dominated by sal in Similipal Tiger Reserve in Odisha, Gandhi and Sundarapandian (2014) from dry deciduous forests of Tiruvannamalai in Tamil Nadu, Mutiso et al (2015) from (Reddy et al 2008;Mohandass et al 2016). In this study, site I is located in an elevation (530-630 m asl) that is higher than that of site II (317-360 m asl), which could be one of the causes for variation in species diversity.…”
Section: Discussioncontrasting
confidence: 65%
“…The values of the basal area of adult woody vegetation recorded in the present study are higher than the values obtained for low elevation forest, but lower than the values of mid-elevation forest and high elevation forest, in pertinence to the study conducted in the tropical forests of Kanyakumari by Swamy et al (2000). The values of the basal area are also higher than those observed by Gandhi and Sundarapandian (2014) and Gupta and Kumar (2014). The values were comparable with other reports (Sundarapandian and Karoor 2013;Murthy et al 2016), but lower than the values recorded by Davidar et al (2007), Bharathi and Prasad (2015) and Mohandass et al (2016).…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, soil differs across habitats, through which P. juliflora has been documented to exhibit extreme variations in establishment and stand density in the Caatinga dry forest (Bailis & McCarthy, 2011). Prosopis juliflora stands have been reported with densities as high as 140.39 stems per ha across flooding plains and alluvial deposits at the Keoladeo National Park in Rajasthan, India (Mukherjee, Velankar & Kumara, 2017) and in Tamil Nadu, India (Gandhi & Pandian, 2014). Such dense monospecific stands suggest soil conditions and seedling ecology as potential key drivers for this invasive species as previously documented for other regions in which Prosopsis species are invasive (Ansley, Zhang & Cooper, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…High species richness is one of the characteristic features of the wet tropical ecosystem (Parsons and Cameron, 1947 ., 2016). The variation in species composition, families and stand structure may be attributed to the location of the study sites, the surface area of the forest, microclimate, availability of water, intensity of grazing, the intensity of human activates etc., (Gandhi and Sundarapandian, 2014). However, total species (Cleghorn, 1861) and slowly replaced by A. latifolia due to their fire tolerant mechanism.…”
Section: Discussionmentioning
confidence: 99%